Role of carbon fiber in the electrothermal behavior and geopolymerization process of carbon fiber-reinforced FA-GBFS geopolymer composite. (10th March 2023) - Gu, Gonghui; Pei, Yaowen; Ma, Tao; Chen, Feng; Zhang, Jinglin; Xu, Fang
Highlights: Gullies on carbon fibers can provide nucleation sites for precursors. Accelerated dissolution of precursors intensifies chemical reactions in CFFGC. The percolation threshold of carbon fiber is 0.4 wt% in this study. Carbon fibers in CFFGC tend to agglomerate when the amount exceeds 0.4 wt%. Abstract: Carbon fiber-reinforced geopolymer composite (CFGC) can be used as the energy conversion layer of airport pavement, thus converting electromagnetic energy into heat energy via induction heating technology to melt snow and ice on pavement surface. In this study, fly ash (FA), granulated blast furnace slag (GBFS) and carbon fibers were used to prepare carbon fiber-reinforced FA-GBFS geopolymer composite (CFFGC). Then, the modification mechanism of carbon fibers on the electrothermal and mechanical properties of CFFGC was studied, in which important effects arising from the geopolymerization process within CFFGC were focused on. Results show that the gullies on carbon fiber surface can provide nucleation sites for the geopolymerization and calcium silicate hydration reaction in CFFGC, which accelerates the precipitation of reactive Si(OH)4 and [Al(OH)4 ] - in the raw materials and promotes the generation of geopolymer gels and CSH gels, thus enhancing the mechanical performance of CFFGC. In addition, when the carbon fiber dosage reaches 0.4 wt%, a substantial conductive network is formed inside CFFGC, which shortens the conductive path and greatly improves the charge transfer capability in CFFGC. Once the carbon fiber dosage exceeds 0.4 wt%, the agglomerated carbon fibers within CFFGC can intensify the phonon scattering, thus reducing its thermal conductivity.